Cyclin E overexpression confers resistance to trastuzumab through noncanonical phosphorylation of SMAD3 in HER2+ breast cancer. Issue 11 (1st November 2020) - Decker, Joseph T.; Kandagatla, Pridvi; Wan, Lei; Bernstein, Regan; Ma, Jeffrey A.; Shea, Lonnie D.; Jeruss, Jacqueline S.
ABSTRACT: The efficacy of trastuzumab, a treatment for HER2+ breast cancer, can be limited by the development of resistance. Cyclin E (CCNE) overexpression has been implicated in trastuzumab resistance. We sought to uncover a potential mechanism for this trastuzumab resistance and focused on a model of CCNE overexpressing HER2+ breast cancer and noncanonical phosphorylation of the TGF-β signaling protein, SMAD3. Network analysis of transcriptional activity in a HER2+, CCNE overexpressing, trastuzumab-resistant cell line (BT474R2) identified decreased SMAD3 activity was associated with treatment resistance. Immunoblotting showed SMAD3 expression was significantly downregulated in BT474R2 cells ( p < .01), and noncanonical phosphorylation of SMAD3 was increased in these CCNE-overexpressing cells. Also, in response to CDK2 inhibition, expression patterns linked to restored canonical SMAD3 signaling, including decreased cMyc and increased cyclin-dependent inhibitor, p15, were identified. The BT474R2 cell line was modified through overexpression of SMAD3 (BT474R2-SMAD3), a mutant construct resistant to CCNE-mediated noncanonical phosphorylation of SMAD3 (BT474R2-5M), and a control (BT474R2-Blank). In vitro studies examining the response to trastuzumab showed increased sensitivity to treatment for BT474R2-5M cells. These findings were then validated in NSG mice inoculated with BT474R2-5M cells or BT474R2 control cells. After treatment with trastuzumab, the NSG mice inoculated with BT474R2-5M cells developed significantly lower tumor volumes ( p < .001), when compared to mice inoculated with BT474R2 cells. Taken together, these results indicate that for patients with HER2+ breast cancer, a mechanism of CCNE-mediated trastuzumab resistance, regulated through noncanonical SMAD3 phosphorylation, could be treated with CDK2 inhibition to help enhance the efficacy of trastuzumab therapy.